TUBING STRENGTH ANALYSIS AND FAILURE ASSESSMENT OF ELECTRICAL SUBMERSIBLE PUMP (ESP) WELL: A CASE STUDY ON PRODUCTION WELL “X” - Brian Tony; Steven Chandra (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
This study will discuss the evaluation of tubing strength in Well X that using Electrical Submersible Pump as an artificial lifting method. The evaluation will be carried out to determine the risk of failure of production tubing due to erosional damage and the failure due to loads on tubing during production operation using Electrical Submersible Pump. Burst, collapse, and tension loads will be the main focus in evaluating the tubing load by considering the worst conditions that may be experienced during production operation. The calculation of the tubing load is done using Microsoft Excel. The result of tubing load calculation will be compared with the tubing rating based on tubing grade. Erosional damage prediction is carried out using software to determine the erosional velocity on the production tubing.This study will evaluate the production tubing used in Well X with an outer diameter of 3.5 inch and L-80 tubing grade. Tubing L-80 has a burst rating of 7240 psi, a collapse rating of 10533.92 psi, and a tension rating of 107581.11 lbf. Tubing is rating will be the limit that determines the integrity of the well during the production period. Based on the evaluation result, L-80 production tubing that using Electrical Submersible Pump as an artificial lifting method is able to withstand the burst load, collapse load, tension load, and the erosional effect of the produced fluid. Therefore, the Electrical Submersible Pump in Well X as an artificial lift system can be carried out without changing the grade of the existing tubing production.